Third generation training: an empirical investigation - Nelson, Tristan, author; Kraiger, Kurt, advisor; Gibbons, Alyssa, committee member; Cleary, Anne, committee member; Henle, Chris, committee member (Colorado State University. Libraries, 2012)
Kraiger (2008b) outlined the differences between first, second, and third generation approaches to training design, and described the potential benefits of a third generation approach. The present study extends this work by further defining the components of a third generation approach and comparing it to a first generation approach using three commonly examined dependent variables: recall, near transfer, and far transfer. Results show no significant differences in trainee performance for participants in either the first or third generation training condition.
Keywords: training; third generation; training design; collaborative learning; social constructivism